The Role of LiTDI Additive in LiNi1/3Mn1/3Co1/3O2/Graphite Lithium-Ion Batteries at Elevated Temperatures. Issue 2 (1st January 2018) - Xu, Chao; Jeschull, Fabian; Brant, William R.; Brandell, Daniel; Edström, Kristina; Gustafsson, Torbjörn
Abstract : The poor thermal stability of conventional LiPF6 -based electrolytes is one of the major obstacles for today's lithium-ion batteries. Recently, lithium 4, 5-dicyano-2-(trifluoromethyl)imidazolide (LiTDI) has demonstrated to be highly efficient in scavenging moisture from the electrolyte and thereby improving electrolyte stability. In this context, effects of the LiTDI additive on LiNi1/3 Mn1/3 Co1/3 O2 (NMC)/graphite cells are evaluated at a temperature of 55°C. With the incorporation of LiTDI, an improved cycling performance of NMC/graphite cells was achieved, and the impedance increase at the NMC/electrolyte interface was significantly mitigated. Furthermore, LiTDI exhibited a profound influence on the interfacial chemistries in the full cell, and LiTDI-derived species were found on the surfaces of both the cathode and the anode. The SEI layer formed on graphite anodes was more homogenous in morphology and consisted of larger amounts of LiF and fewer oxygen-containing species, as compared to graphite in additive-free cells. This study shows that LiTDI is a promising electrolyte additive for NMC/graphite cells operated at elevated temperatures, highlighting that the influence of the LiTDI additive is worth exploring also in other battery chemistries.